Decolonizing sport - Forsyth, Janice; O'Bonsawin, Christine; Field, Russell; Phillips, Murray G. (Fernwood Publishing, 2023)
"The path to decolonization is difficult and complex, and can even be contradictory at times, as when an Indigenous community enlists the same corporate sponsor that will destroy its natural environment to provide sport programming for its youth. There is no easy way forward. The Black Lives Matter movement, and their massive followers on social media, propelled forward discussions about the inequities that Covid-19 highlighted with unprecedented momentum. Indigenous people in Canada voiced their concerns in solidarity, calling attention to disparities they faced in everything from impoverished Indigenous health care initiatives to the overrepresentation of Indigenous people in the Canadian justice system, demanding to be heard alongside systemic change. Structural adjustments were afoot, including changes in the professional sport leagues."
Includes bibliographical references and index
Keywords: Rassismus; Indigenes Volk; Entkolonialisierung; Sport; Racism in sports; Sports / Social aspects; Decolonization; Indigenous peoples / Recreation; Indigenous peoples / Games; Sports / History; First Nations - Sports; Indigenous athletes - Canada; Racisme dans les sports; Sports - Aspect social; Décolonisation; Sports - Histoire; Indigenous peoples; Sports; Sports - Social aspects; Games; History; Aufsatzsammlung